Proposta para melhoramento de bancada experimental de flambagem - Viana, Pedro Henrique Pinto Tôrres (Universidade Federal Rural do Semi-Árido, 2019)
This study aimed to promote improvements of an experimental bench constructed by a student of the Federal Rural Semi-Arid Federal University - UFERSA, Caraúbas campus, in order to improve the methodology of teaching / learning in the classroom of the discipline of Resistance of Materials II. The work was developed based on the concepts of buckling of columns of Euler, subject present in the menu of the discipline, and its main motivation was to allow the students to understand the subject in practice, through experiments using the didactic experimental group involving the presented contents in the classroom, arousing the student's interest in content and improving learning. When it was executed, they sought to facilitate the visualization and understanding of the students regarding the phenomenon of buckling of columns, submitted to different configurations of support. However, in order to reduce the experimental errors existing in the first design, such as increase in friction due to oxidation of the support pieces, errors in measurements due to clear support supports of the test columns, we sought in this work means for the improvement of this machine, increasing the precision and the quality of these experiments, helping the teacher better in the transfer of knowledge in a practical and intuitive way.
Monografia
Keywords: Bancada experimental; Flambagem; Colunas de Euler; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA